Spring migration, March 1-May 24, 1984, contributed by Peter C. Petersen - Petersen, Peter C.et al (1984)
Spring migration, March 1-May 24, 1984, were field notes contributed by Peter C. Petersen, with nine other observers. Highlights were a Red-throated Loon at Cedar Lake and Greater Scaups at Goose Lake. A Pine Siskin at Fairmont Cemetery was seen carrying nesting material. First page said 1983, but this item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of spring 1984. Epson - sheet feed/flatbed